Sterile neutrophilic dermatitis in a cat associated with a topical plant‐derived oil flea preventative. Issue 1 (1st September 2021) - Zhou, Zijin; Noland, Erica; Rosser, Edmund; Petersen, Annette
Abstract : A 4‐year‐old, female spayed, domestic short hair cat presented with an acute eruption of pustules and bullous plaques after application of a plant‐based, essential oil flea preventative. Histopathological evaluation of biopsies revealed severe neutrophilic infiltrate within the dermis and culture was negative. The cat's skin lesions responded rapidly to glucocorticoid monotherapy. Abstract : A 4‐year‐old, female spayed, domestic short hair cat presented with an acute eruption of pustules and bullous plaques after application of an essential oil flea preventative. Histopathological evaluation of biopsies revealed severe neutrophilic infiltrate within the dermis and culture was negative. The cat's skin lesions responded rapidly to glucocorticoid monotherapy. Résumé: Un chat européen de 4 ans, femelle stérilisée, est présenté avec une éruption aigue de pustules et de plaques bulleuses après application d'huiles essentielles anti‐puces. L'examen histopathologique de biopsies révèle un infiltrat neutrophilique sévère au sein du derme et la culture était négative. Les lésions cutanées du chat ont rapidement répondu à une corticothérapie. Resumen: Una gata doméstica de pelo corto esterilizada de 4 años de edad presentó una erupción aguda de pústulas y placas vesiculares después de la aplicación de un preventivo de pulgas con aceite esencial. La evaluación histopatológica de las biopsias reveló un infiltrado neutrofílico severo dentro de la dermis y el cultivo fue negativo. Las lesiones cutáneas del gato respondieron rápidamente a la monoterapia con glucocorticoides. Zusammenfassung: Eine 4 Jahre alte weibliche kastrierte Kurzhaarkatze wurde mit einem akuten Ausbruch von Pusteln und bullösen Plaques nach Applikation einer aus essentiellen Ölen bestehenden Flohprophylaxe vorgestellt. Eine histopathologische Evaluierung der Biopsien zeigte ein hochgradiges Infiltrat an neutrophilen Granulozyten in der Dermis; eine Kultur war negativ. Die Hautläsionen der Katze reagierten rasch auf eine Glukokortikoid Monotherapie. 要約: 4歳, 避妊メス、ドメスティック・ショートヘアー・キャットが, エッセンシャルオイルのノミ予防薬を塗布した後に, 膿疱および水疱性プラークの急性発疹を呈した。生検による病理組織学的評価では, 真皮内に重度の好中球浸潤を認め, 培養は陰性であった。この猫の皮膚病変はグルココルチコイドの単剤療法に速やかに反応した。 摘要: 1只4岁雌性绝育短毛猫在用一种精油跳蚤预防剂后, 出现脓疱和大疱性斑块的急性皮疹。活检组织病理学评估显示真皮内中性粒细胞大量浸润, 培养结果为阴性。糖皮质激素单药治疗猫的皮肤病变快速有效。 Resumo: Uma gata doméstica de pelo curto castrada, de quatro anos de idade, foi apresentada com um quadro agudo de erupção de pústulas e placas bolhosas após a aplicação de um óleo preventivo de pulgas. A avaliação histopatológica dos fragmentos de biópsia revelou grave infiltrado inflamatório neutrofílico na derme e a cultura foi negativa. As lesões cutâneas da gata responderam rapidamente à monoterapia com glicocorticoides.